Ask Your Question

Revision history [back]

click to hide/show revision 1
initial version

You can try the following with substituting b-a with c

eq1 = (sqrt((c)^2 + (B-A)^2) == A+B)

which results in

[c == -2*sqrt(A*B), c == 2*sqrt(A*B)]

But can anybody explain me the results of the computation without the assume statements? For A,B both beeing negative the solver does not do anything and for A being bigger and B being smaller then zero, sage throws an error that maxima needs further inputs (the same as when you're not using assume)